(untitled) (Journal of Philosophy Culture and Political Science, 2019)
Abstract. Most theories about the negative relationship between Islam and democracy relyon an interpretation of the Islamic political tradition. More positive accounts are also anchored in the same tradition, interpreted in a different way. While some scholarship relies on more empirical observation and analysis, there is no single work which systematically demonstrates the relationship between Islam and democracy.This study is an attempt to fi ll this gap by defi ning Islam empirically in terms of several components and democracy in terms of the components of democratic culture-social capital, political tolerance, political engagement, political trust, and support for the democratic system-and political participation. The theories which assert that Islam is inimical to democracy are tested by examining the extent to which the Islamic and democratic components are negatively associated. This study found that Islam defi ned by two sets of rituals, the networks of Islamic civic engagement, Islamic social identity, and Islamist political orientations (Islamism) does not have a negative association with the components of democracy. The only negative relationship is found between Islamism and tolerance toward Christians. Keywords: spiritual culture, new values, world landmarks, Islamic culture.